(untitled) (Medico Legal Update, 2021)
The main feature in multiple myeloma is osteolysis and, hence, bone turnover markers have got the at most care in different studies on this disease. The present paper would stress on the calculation of free progression survival indices using some of these markers . Sixty-five MM (males=41, females=24) patients distributed to different hematologycenters in Iraq were enrolled in this study. Their age range was 39-81 years, they were distributed all on three stages of the diseaseaccording to the international staging system (ISS) : Group A – Stage I (n=21 patients, age mean 57.14±12.25 years), Group B – Stage II (n=22 patients, age mean of 56.45±11.33 years), and Group C-Stage III (n=22 patients, age mean 60.59±11.55 years). Blood samples were taken from each patient just prior to starting the chemotherapy for the measurement of blood hemoglobin (Hb), serum Creatinine, Calcium, ?2 Microglubulin, Osteocalcin (OC), total and Beta C-terminal telopeptide (CTX, BCTX), Parathyroid hormone (PTH), Syndecan-1 (CD138), and both kappa & lambda free light chain (FLC?, FLC?). There was no significant association between age, sex, body weight and residency with disease staging or progression. From the bone markers studied only CTX and BCTX were significantly associated with the disease progression and showing varying free progression patient survival times with CTX and BCTX at different concentrations. The comparison between the results of the newly diagnosed and long-standing patients revealed that only total FLC, FLC?, FLC? and CD138 were significantly higher in the long-standing patients. Their sensitivity and specificity values were varying among these markers.